The Application of Hamzah in Surah Al-Ahqaf in a Comparative Method - Ismati , Sayyid Azimullah; Rayiq, Naqeebullah (Journal of Social Sciences - Kabul University, 2022)
In the Arabic language, hamzah takes various forms and has specific applications. Arabs articulate and categorize it differently, distinguishing between the strong hamzah and the light or softened hamzah. It appears in four forms: pronounced, omitted, softened, and substituted. The investigation of hamzah is significant due to its relevance in a Bedouin linguistic environment, where it is described as a loud or intense sound—one of the explosive throat sounds, neither whispered nor muffled. The articulation of hamzah in Bedouin culture aligns with their natural speech patterns, as they tended to pronounce it forcefully. However, at times, they softened or facilitated its pronunciation. In conveying meaning, hamzah appears in multiple forms: as a silent hamzah, a silent hamzah following a fatḥah, a moving hamzah, a moving hamzah preceded by a moving letter, a moving hamzah preceded by a silent letter, a broken hamzah preceded by an alif, a broken hamzah preceded by a silent letter, and an open hamzah preceded by a silent letter. This article examines these variations in hamzah's articulation and aims to substantiate these claims by analyzing its usage in Surah Al-Ahqaf through a comparative approach.